Qur'anic Counseling with Motivational Guidance QS. Al-Baqarah Verses 155-156, in Overcoming Anxiety in One of the Students - Sholihah, Maidahtus; Cholil; Ningsih, Yusria (Dirasah International Journal of Islamic Studies, 2024)
Anxiety is a psychological problem that is often experienced by students and can interfere with their learning process. At Sunan Ampel State Islamic University (UINSA) Surabaya, applying Qur'anic-based counseling methods is essential in Islamic education. Research Objectives: This study aims to evaluate the effectiveness of Quranic counseling based on the motivation of QS. Al-Baqarah verses 155-156 in overcoming anxiety in one of the students at UINSA. Methods: This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and analysis of counseling documentation. QS. Al-Baqarah verses 155-156 were used as the basic framework for the counseling session, which included discussions about patience and steadfastness in facing life's trials. Results: The results showed a significant decrease in anxiety levels in university students after attending a series of Quranic counseling sessions. Students reported an increased sense of calmness and a deeper understanding of the importance of patience in facing challenges. Conclusion: Qur'anic counseling based on QS. Al-Baqarah verses 155-156 effectively overcome anxiety in university students at UINSA. The findings indicate that Qur'an-based spiritual approaches can effectively provide psychological support to university students in Islamic educational institutions.